A Study on the Impact of Coffee Service Quality on Customer Satisfaction and Loyalty (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Coffee is a representative food service industry that commonly satisfies basic human needs. Among the consumers, the younger generation consumption is relatively higher than the middle and elderly generations. Their purchase decision is based on the individuality and unique characteristics of the coffee shop e.g., sophisticated internal environment, quality drinks, discriminatory marketing, and diverse menus. Coffee shops serve a variety of purpose including providing simple meals, a place to study, an area to work, and a comfortable rest area. This study conducted an empirical analysis on the factors affecting the purchase decisions of the coffee consumers. The results imply the following hypothesis: (H1-1) interaction influences positive emotions was adopted; (H1-2) the physical environment influences positive emotions was rejected; (H1-3) the result quality influences positive emotions was adopted; (H1-4) representativeness affects positive emotions was adopted; (H1-5) diversity influences positive emotions was adopted, and; (H2) positive emotions influence loyalty was adopted.